Close-Range Photogrammetry and 3D Imaging - Luhmann, Thomas (De Gruyter Textbook, 2013)
This is the second edition of the established guide to close-range photogrammetry which uses accurate imaging techniques to analyse the three-dimensional shape of a wide range of manufactured and natural objects. After more than 20 years of use, close-range photogrammetry, now for the most part entirely digital, has become an accepted, powerful and readily available technique for engineers, scientists and others who wish to utilise images to make accurate 3D measurements of complex objects. Here they will find the photogrammetric fundamentals, details of system hardware and software, and broad range of real-world applications in order to achieve this. Following the introduction, the book provides fundamental mathematics covering subjects such as image orientation, digital imaging processing and 3D reconstruction methods, as well as a discussion of imaging technology, including targeting and illumination, and its implementation in hardware and software. It concludes with an overview of photogrammetric solutions for typical applications in engineering, manufacturing, medical science, architecture, archaeology and other fields.